The Effect of Biological Control Agents on Paddy Soil Bacterial Community Structure - Aisyah Surya Bintang; Arif Wibowo; Achmadi Priyatmojo; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 2022)
Biodiversity has been defined as the range of significantly different types of organisms and their relative abundance in an assemblage of community. The aim of this research was to understand about soil bacterial community after on biological control agents (BCA) treatments with various formulations. This research was conducted at Sleman Regency, Special Region of Yogyakarta and Faculty Agriculture of Universitas Gadjah Mada. The research conducted with culture dependent and culture independent methods to assess soil bacterial diversity. The results showed that soil bacterial diversity before and after treatment of biological control agent were different. Results from this research suggested different molecular methods regarding soil bacterial diversity based on their benefits and challenges.